Biology - Mader, Sylvia S. (Boston : WCB/McGraw-Hill, 1998)
[This text] covers the concepts and principles of biology from the structure and function of the cell to the organization of the biosphere. It draws upon the entire world of living things to bring out an evolutionary theme that is introduced from the start. The concept of evolution is necessary to understanding the unity and diversity of life and serves as a background for the study of ecological principles. Four chapters are devoted to reviewing the ecological principles that explain how the natural world works. Frequent references are made as to how humans impact the environment. Ecological problems are considered.
The cell. Genetic basis of life (Meiosis, sexual reproduction, chromosomes, genes, DNA). Evolution. Behavior and ecology. Diversity of life. Classification of living things. Viruses, bacteria, archaea. Protists. Fungi. Plants. Animals (Invertebrates, protostomes, Deuterostomes). Plant structure and function. Animal structure and function. Homeostasis. A view of life. How to define life. Evolution. Ecosystems contain populations. Tropical rainforests: can we live without them? How living things are classified. The process of science. Basic chemistry. Matter is composed of elements. Atoms form compounds and molecules. Water is essential to life. Ecology focus: The harm done by acid deposition. The chemistry of life. Cells contain organic molecules. Carbohydrates. Lipids. Proteins. Nucleic acids. Cell structure and function. Cells make up living things. Prokaryotic cells. Eukaryotic cells. Membrane structure and function. Membrane models have changed. Plasma membrane. Cell surface. Metabolism: energy and enzymes. Metabolic reactions and energy transformations. Metabolic pathways and enzymes. Photosynthesis. Sunlight provides solar energy. Photosyntheses occurs in chloroplasts. Solar energy is captured. Carbohydrate is synthesized. Cellular respiration. How cells acquire ATP. Outside the mitochondria: glycolysis. Inside the mitochondria. Metabolic pool and biosynthesis. Fermentation. Genetic basis of life. Prokaryotic cells. Eukaryotic chromosomes. Eukaryotic cells. Meiosis and sexual reproduction. Meiosis has phases. Human life cycle. Mendelian patterns of inheritance. Gregor Mendel. Monohybrid cross. Dihybrid cross. Chromosomes and genes. Mutations. Human genetics. Autosomal traits. Sex-linked traits. DNA: the genetic material. Gene activity. How genes code for amino acids. Transcription. Translation. Mutations. Regulation of gene activity. Prokaryotes utilize operons. Eukaryotes utilize various methods. Cancer is a failure in genetic control. Prevention of cancer. Recombinant DNA and biotechnology. Cloning of a gene. Biotechnology products. Making transgenic organisms. Gene therapy. Human chromosomes. Evolution. Darwin develops a theory. Process of evolution. Speciation. Origin and history of life. Human evolution. Primates. Primate are diverse. Hominids break away. Animal behavior. Animals are social. Sociobiology. Ecology of populations. Population size. Life history patterns. Human population growth. Community ecology. Biological community. Communities are organized. Community structures. Community biodiversity. Ecosystems. Energy flow and nutrient cycling. Global biogeochemical cycles. Water cycle. Carbon cycle. Nitrogen cycle. Phosphorus cycle. Cause of pollution. The biosphere. Biomes. Terrestrial biomes: tundra, coniferous forests, temperate deciduous forests, tropical forests, shrublands, grasslands, deserts. Aquatic biomes: lakes, coastal communities, oceans, coral reefs. Human impact on the global environment. Human population and industrialization. Global climate change. Global chemical climate. Stratospheric ozone depletion. Surface waters, aquifers, oceans: pollution of surface waters and oceans. Soil erosion, desertification and deforestation. Human impact on diversity. Classification of living things. Organisms. Constructing phylogenetic trees. The number of kingdoms. Viruses, bacteria and archaea. The protists. Algae. Protozoa. Slime molds and water molds are funguslike. The fungi. Symbiotic relationships. The plants. Nonvascular plants. Vascular plants include seedless and seed plants. Ferns and allies. Gymnosperms. Angiosperms. Plant life cycles. Animals: introduction to invertebrates. How animals evolved and are classified. Multicellularity evolves. Tissue layers evolve. Bilateral symmetry evolves. A pseudocoelom evolves. Coelom. Animals: the Protostomes. A coelom. Three-part body plan. Segmentation evolves. Jointed appendages evolve. Protostomes. Animals: the Deuterostomes. Radial symmetry. Chordate characteristics evolve. The vertebrate body plan evolves. The amniote egg evolves. Wings and feathers evolve. Homeothermy pays off. Plant structure. Plants have organs. Monocot versus Dicot plants. Plant organs have tissues. How roots are organized. How stems are organized. How leaves are organized. Nutrition and transport in plants. Inorganic nutrients. How water moves through a plant. How organic nutrients are transported. Growth and development in plants. Plant responses to stimuli. Plant hormones. The photoperiod controls seasonal changes. Phytochrome. Reproduction in plants. Flowering plants. Sporophyte structure. Gametophytes. The embryo develops in stages. The seeds are enclosed by fruit. Plants can reproduce asexually. Animal structure and function. Animal organization and homeostasis. Animals are organized: epithelial, connective, muscular and nervous tissue conducts. Organs have structure and functions. Circulation. Transport in invertebrates. Transport in vertebrates.Transport in humans. Cardiovascular disorders in humans. Hypertension. Atherosclerosis. Stroke and heart attack. Blood as transport medium. Know your blood type. Lymph transport and immunity. Lymphatic system helps cardiovascular system. Plasma cells. Antibodies. The Aids epidemic. Immunity can be induced and has side-effects. Allergies. Tissue rejection. Digestion. Digestive tracts. Humans have a complete tract. Digestive juices. Nutrition affects health. Respiration. How animals exchange gases. How humans breathe. Osmotic regulation and excretion. Osmotic regulation. Nitrogenous waste products. Organs of excretion. Urinary system. Neurons and nervous systems. Nervous tissue. Alzheimer and Parkinson disease. How the nervous system evolved. The peripheral nervous sytem. Central nervous system: brain and spinal cord. Drugs of abuse. Sense organs. Sensing chemicals. Sensing light. Sensing mechanical stimuli. Support systems and locomotion. Comparing skeletons. Humans have an endoskeleton. Osteoporosis. How muscles function. Hormones and endocrine systems. Cellular metabolism. Human Endocrine system. Hypothalamus. Thyroid gland. Parathyroid glands. Adrenal glands. Insulin. Insect growth hormones. Environmental signals in three categories. Reproduction. How animals reproduce. Males have testes. Females have ovaries. Humans vary in fertility. Birth-control methods. Development has stages. Cells become specialized and embryos take shape. Humans are embryos and then fetuses. Periodic table of the elements. Metric system. The five kingdom system of classification: Kingdom Monera (prokaryotic unicellular organisms), Kingdom Protista (eukaryotic unicellular microorganisms), Kingdom Fungi (multicellular eukaryotes), Kingdom Plantae (multicellular), Kingdom Animalia (multicelluar organisms).
Index
Includes bibliographical references and index.
Keywords: Biology